Essentials of international relations - Mingst, Karen A. (New York : W. W. Norton, 1999)
Approaches to international relations. The historical context of contemporary international relations. Contending perspectives. The international system. The State. The individual. War and strife...
Keywords: International relations; Diplomacy; International relations